Market Growth and Barriers to Entry: Evidence from the Title Insurance Industry - Boyer, Martin; Nyce, Charles M. (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2010)
The purpose of this paper is to examine barriers to entry in an insurance market wherein banks are an integral part of the distribution system: Title insurance. Given that the title insurance industry is characterized by two major entry barriers, controlled business arrangements and title plants, we test different industrial organization growth models with barriers to entry to determine which model best describes the title insurance industry. The empirical analysis we present suggests that the theoretical model that explains more accurately the current title insurance industry structure is the Salop circular-city model.